Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor